Current issues of a historical poem - Rakhimov B.S., Aitbayeva B.M.,; Zharylgapov, Zhansaya; Zhanar Rustemova, Sarzhan Takirov, (Opción, 2019)
In this research, we are talking about the Kazakh epos in which the comparative method is widely used. As a result, the storyline is followed, where ethnic, religious viable concepts in every age, poetry always connected to changes in the data. In conclusion, the Kazakh epic seemed to be one of the heroes in the form of a melody and then moved to the interim nature of the lyrical and epic, and not the nature of the genre with a new quality of the poem.